Correlations among parameters of growth analysis of tomato cultivars (Lycopersicon esculentum Mill) - Martins, Gilberto; Vasconcellos, Edmar F.C.; Lucchesi, Antonio A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1985)
In the present research it has been studied the possible correlation among the parameters of quantitative analysis of vegetal growth through experimental data from tomato cultivars Kada, Angela, Floradel and Tropic carried out in the tropical-humid conditons of Manaus (Amazon State, Brazil) in a typical regional fashion (open side greenhouses with plants cultived in suspended wooden boxes). Every 14 days plant samples were collected in the seedling time, to determine height, leaf area, dry matter, weight of the plant and fresh and dry matter weight of the fruits, during all the tomato cicle. Thus an analysis was made of the cultivar vegetal growth and the correlation among the evaluated plant parameters : height, yield, dry matter, weight (DMW), leaf area index (LAI), dry matter production rate (DMPR), vegetative dry matter production rate (VDMPR), fruit dry matter production rate (FDMPR), relative growth rate (RGR) and net assimilation rate (NAR). Studying the correlation among the parameters, the height presented the greatest amount of hight correlation, becoming this way a good cross-index to estimate the plant growth. The positive correlations are: a) Height With LAI, with yield, with DMW and with DMPR , that is, these parameters were directly cor relationed with the height; b) DMW with yield and LAI. The NAR presented all coeficient correlations with low rates and among these rates the highest was with the RGR, showing this way to be affected by this parameter. The RGR only had high correlations with the height and the LAI, these correlations being negative, that is, while the plant grows, the RGR decreases. The most productive cultivars presented high positive correlations between FDWPR and DWPR, showing that the economic productivity is directly affected by the biological productivity in the cultivars.